Sosialisasi Undang-Undang No 23 Tahun 2002 Tentang Perlindungan Anak Mencegah Cyberbully - Sari, NurulLita; Rosini, Nanik Ida; Widiastuti, Putri; Hanindita, Kafka; Sa’adah, Adinda Lailatus (Kurnia Mengabdi: Jurnal Pengabdian kepada Masyarakat, 2024)
This research aims to provide an understanding of Law No. 35 of 2014 concerning child protection to prevent Cyberbullying and provide an understanding of the types, negative impacts, and prevention efforts related to Cyberbullying. This research method involves the student council of SMP NEGERI 1 Ciseeng with the implementation of socialization for two days. On the first day, the material was given about the socialization of the Law and on the second day the material was given about cyberbullying. The results showed that some student council members had experienced cyberbullying, they did not understand how to deal with the problem and overcome the trauma and how to report to the authorities. The success indicators in this community service activity increase students' understanding of the child protection law and also the prevention of cyberbullying. The students were also enthusiastic and actively participated in the smooth running of the event with a Q&A session. The results of the study showed a significant effect between the Pre-Test and Post-Test after the presentation of the material that had been delivered. In conclusion, if W count < W table then H0 is rejected or there is a difference between the Pre-Test and Post-Test.